Английский язык: учебник - Матюшкина-Герке Т. И. Тамара Ивановна; Балашова С. П. Светлана Пантелеймоновна; Броссе Н. Н. Наталия Николаевна; Иванова Л. Л. Лидия Лукинична; Кузмичева Т. Н. Татьяна Павловна; Чахоян Л. П. Людмила Павловна (Москва, Высшая школа, 1990)
Авт. указаны на обороте тит. л.